EFFECT OF ESCAPE VENT ON CATCHABILITY AND SELECTIVITY OF POT FOR BLACK DAMSEL (Neoglyphidodon melas) - Dahri Iskandar (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The objective of this study was to investigate the effect of escape vent on catch of black damsel, then sizeselectivity of escape vent will be estimated to predict the retention probability of escape vent on black damsel.The result of this study indicated that comparison of diversity index between the catches of escape vent potsand non escape vent pots were 3.07 and 3.38 respectively. Installing escape vent pots significantly impovecatch of commercial size black damsel i.e 56.6% of total catch. A Kolmogorov-Smirnov two sample testindicated that there is significant difference on the length distribution of black damsel between escape ventpots and unvented pots. The result of size selectivity curve indicated that fish size smaller than 8 cm lengthhave high probability to escape from escape vent pots. Length at 50 % retention occurs at fish length of 14.67 mm.